ANALYSIS OF THE POLITICAL AND SOCIAL IMPACT OF THE DISMISSAL OF JOKOWI, GIBRAN, AND BOBBY NASUTION FROM PDIP ON POWER DYNAMICS IN INDONESIA - Dwi Novita Asari, Fitria; Gendhis Hasmantri, Khoirunnisa; Fazahra, Alicya; Puspita Nasywaini, Diva (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN-COMMUNITY OF RESEARCH LABORATORY, 2024)
The dismissal of Joko Widodo (Jokowi), Gibran Rakabuming Raka, Bobby Nasution from the Indonesian Democratic Party of Struggle (PDIP) became a shocking event and caused a big impact on Indonesian politics. This research aims to analyze how the dismissal of these three figures affects the dynamics of power in Indonesia, both from the political and social sides. This dismissal raises various questions about internal relations in PDIP, the party's political strategy, and its impact on public support for the three figures. This study also looks at how this event affects political stability at the national and local levels, and how this change can affect future political support patterns. By using a qualitative approach, this study explores the various effects of this dismissal on Indonesia's political map, both in the short and long term.